TAUHID SEBAGAI PRINSIP DASAR DALAM PENGELOLAAN KEUANGAN SYARIAH - Audina Fitri Pohan; Ferizal; Bagus Pratama Nasution; Ivan Rivaldi; Hidayati; Namira Suci Shafira; Rezeki Mustafa Lubis; Risqi Muhtadi Siahaan; Zakiatun Afifah Hasibuan (CV. BAROKAH PUBLISHER, 2026)
The aim of this research is to investigate effective strategies and solutions in managing islamic finance by managing finances to overcome financial challenges. This research method involves an in-depth literature review on the practice of building a country’s economy with morals and social justice under the protection of Allah SWT. The results of this research show that good financial education, setting clear financial goals, creating an orderly budget and wise debt management creates a framework for economic growth, the safety of a harmonious life, in the face of ongoing economic changes, is very important in understanding strategies for managing sharia money. The basic values of islamic economics consist of: the value of ownership, the value of justice, the value of balance, the value of freedom,the value of togetherness. These business principles and ethics are the operational basis for sharia financial institutions in indonesia, where economic value is contained in something about an economic condition in a country. To restore equality there must be justice in the country so that deflation does not occur due to somethng that deviating in a country will result in fatalities in that country.